Electrospray ionization-ion mobility spectrometry–high resolution tandem mass spectrometry with collision-induced charge stripping for the analysis of highly multiply charged intact polymers. Issue 10 (23rd April 2019) - Ozeki, Yuka; Omae, Mizuki; Kitagawa, Shinya; Ohtani, Hajime
Abstract : Analysis of highly multiply charged polymers by IMS-MS/MS with collision-induced charge stripping. Abstract : Polymers with large molecular weight are difficult to interpret using electrospray ionization-mass spectrometry (ESI-MS) due to the generation of various highly multiply charged analytes. Although ESI-ion mobility spectrometry (IMS)-MS is effective in reducing the complexity of the mass spectrum, this approach is insufficient for analyzing highly multiply charged polymers. In this study, we propose a method combining tandem mass spectrometry (quadrupole and high-resolution time-of-flight MS, QMS/TOFMS), IMS, and collision-induced charge stripping (CICS) for analyzing large intact polymers (∼40 kDa), which are highly multiply charged. The number of charges can be estimated from a Fourier transform power spectrum of a mass spectrum when the charge number is less than approximately 20. Interpretations of the spectra of poly(ethylene oxide)s (PEOs) weighing 20 kDa, poly(methyl methacrylate)s weighing 22 kDa, and methoxy-PEO-maleimide weighing 40 kDa were successfully demonstrated with isotope level and polymerization degree level separations, respectively. In the proposed method, a mixture can be analyzed for relatively small (a few kDa) and large (a few tens of kDa) polymers simultaneously without any sample pretreatment.